Detectability of Timed Discrete Event Systems - Chengshi Miao (IEEE Access, 2023)
This paper introduces T-detectability, which extends detectability to timed discrete event systems within the context of communication networks. We propose network T-detectability to address the challenges posed by observation delays and losses in network environments. Our approach involves the construction of an augmented automaton to model delays and losses and an extended automaton to calculate state estimates. We present a method for checking network T-detectability and T-detectability. These findings contribute to a better understanding of system behavior in complex scenarios and provide analytical techniques for assessing detection properties in timed discrete event systems operating within communication networks.